Delayed Recovery of Leg Fatigue Symptoms Following a Maximal Exercise Session in People With Multiple Sclerosis. (February 2014) - Dawes, Helen; Collett, Johnny; Meaney, Andy; Duda, Joan; Sackley, Cath; Wade, Derick; Barker, Karen; Izadi, Hooshang
Background . Fatigue is a chronic symptom for people with multiple sclerosis (PwMS). Objective . Symptoms of fatigue were investigated during and following a single exercise session. Methods. In all, 58 PwMS and 15 healthy, low-active controls performed a cycle ergometer incremental exercise test to voluntary exhaustion. Physiological intensity (expired air and heart rate), perceived breathlessness, and leg fatigue (Rating of Perceived Exertion [RPE] CR-10 Scale) were measured during and for 10 minutes following exercise. Measures of baseline disability (Barthel Index), activity (Physical Activity Scale for the Elderly), vitality (Subjective Vitality Scale), and general fatigue (Fatigue Severity Scale [FSS]) were recorded. Results. PwMS had reduced exercise capacity ( P = .00 to .01), but sensations of breathlessness and leg fatigue were the same at voluntary exercise termination in both groups ( P = .09). PwMS with fatigue (FSS ≥ 4) exhibited reduced exercise capacity ( P = .03 to .05) but reached the same physiological intensity, breathlessness, and leg fatigue symptoms at test termination as nonfatigued peers ( P = .16 to .59). During recovery, there was no difference in observed means between groups, except for leg RPE, which was higher in the MS group ( P = .047) and higher at 3 and 5 minutes after exercise in the fatigued MS group ( P = .02). Physiological markers and breathlessness recovered at the same rate in both groups ( P = .33 to .67). Conclusion . Monitoring leg fatigue symptoms during and through recovery from physical activities may help guide participation in physical activities for PwMS, particularly in people managing high levels of fatigue.